Extraordinary Modernism in the Reconstruction of the City Center of Le Havre on the Example of the Church of St. Joseph According to the Design of Auguste Perret - Szumigała, Paweł Piotr; Szumigała, Karolina Olenia (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2022)
The aim of the work is to reread the extraordinary architectural, structural and aesthetic values of a sacred architectural object from the period of reconstruction of the city center of Le Havre. The research used the method: case study on a selected example of the church of St. Joseph. The scope of research included spatial and structural analyses and material solutions in the context of the reconstruction of the le Havre city centre area carried out in the current of academic modernism. Results: The church building, together with the town hall building and the cathedral, is one of the three main elements of the historical urban composition and the contemporary reconstruction of the city centre of Le Havre carried out by Auguste Perret. The church building in the style of academic modernism is still an inspiring and unusual example of the use of raw material, which are concrete and reinforced concrete in the implementation of a sacred object. The object is an example of modern construction thought, which also plays an artistic role in the creation of the form and interior of the object. The spatial, aesthetic and functional values of reinforced concrete construction and concrete detail are an enduring example of mastery of technology and implementation of spatial vision in this difficult and unattractive building material. To sum up, it should be stated that this object fits into the context of coherent and comprehensive thinking about sacred architecture and urban space reconstructed in reinforced concrete technology during the modernist period. It is a forgotten, but still extraordinary inspiration for contemporary needs in this area.